2009
DOI: 10.1002/ab.20308
|View full text |Cite
|
Sign up to set email alerts
|

Case study of a one‐sided attack by multiple troop members on a nontroop adolescent male and the death of Japanese macaques (Macaca fuscata)

Abstract: An adolescent wild male Japanese macaque (Macaca fuscata), following Kinkazan A troop, was attacked one-sidedly by multiple members of the troop. The victim was identified as PI, and was estimated to be seven+/-one year old. The aggressive interaction was recorded by video camera until the end. Although at least 16 troop members approached PI more than once, only three males (one adult, two adolescents) of A troop attacked him. PI kept crouching throughout the attack, then escaped to the shore and dived into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…First, macaques in the smaller coastal group reduce the risk of injury or death along the border by being in proximity with a large number of group members [Wilson and Wrangham, 2003]. It was reported that lone animals were injured or killed by out-group members, even in species forming cohesive groups [Mech, 1994;Gros-Louis et al, 2003;Shimada et al, 2009]. Second, macaques in the smaller coastal group detect and run away from other groups more quickly along the border because more eyes and ears become available to scan the surroundings [Beauchamp, 2015].…”
Section: Variation In Food Patch Use Based On Food Patch Locationmentioning
confidence: 99%
“…First, macaques in the smaller coastal group reduce the risk of injury or death along the border by being in proximity with a large number of group members [Wilson and Wrangham, 2003]. It was reported that lone animals were injured or killed by out-group members, even in species forming cohesive groups [Mech, 1994;Gros-Louis et al, 2003;Shimada et al, 2009]. Second, macaques in the smaller coastal group detect and run away from other groups more quickly along the border because more eyes and ears become available to scan the surroundings [Beauchamp, 2015].…”
Section: Variation In Food Patch Use Based On Food Patch Locationmentioning
confidence: 99%
“…Separation from group members has several disadvantages, such as increased risk of predation and aggression from conspecifics of other groups [Goodall, 1986;Shimada et al, 2009]. However, each group is usually composed of individuals of different age-sex classes whose requirements and abilities differ [van Schaik & van Noordwijk, 1986].…”
Section: Introductionmentioning
confidence: 99%
“…In some populations, including the population observed for this study, intergroup relationships are agonistic. Severe aggression toward solitary individuals has also occasionally been observed [Shimada et al, 2009]. Thus, the maintenance of group cohesiveness provides an advantage through increased feeding efficiency, whereas leaving a group is disadvantageous because of aggression from conspecifics and intergroup competition.…”
Section: Introductionmentioning
confidence: 99%
“…Many primate species form cohesive groups whose members usually travel together to increase feeding efficiency and to avoid predation [Kappeler & van Schaik, 2002; Kinzey & Cunningham, 1994]. Separation from group members has several disadvantages, such as increased risk of predation and aggression from conspecifics of other groups [Goodall, 1986; Shimada et al, 2009]. However, each group is usually composed of individuals of different age–sex classes whose requirements and abilities differ [van Schaik & van Noordwijk, 1986].…”
Section: Introductionmentioning
confidence: 99%
“…In some populations, including the population observed for this study, intergroup relationships are agonistic. Severe aggression toward solitary individuals has also occasionally been observed [Shimada et al, 2009]. Thus, the maintenance of group cohesiveness provides an advantage through increased feeding efficiency, whereas leaving a group is disadvantageous because of aggression from conspecifics and intergroup competition.…”
Section: Introductionmentioning
confidence: 99%